Mekanisme Koping Pada Pasien Perilaku Kekerasan Dengan Risiko Menciderai Orang Lain Dan Lingkungan - Dwi Prastya, Faishal; , Arum Pratiwi, S.Kp., M.Kes (2017)
Background: Mental disorders can occur in all countries, irrespective of their gender, age, materials, and shelter. Violent behavior is a form of behavior that is intended to injure a person physically and psychologically. Based on these definitions that violent behavior can be done verbally, directed at oneself, others and the environment. Nurses need to identify coping mechanisms so that the client can assist clients to develop constructive coping mechanisms in expressing anger. Coping mechanism that is commonly used is the ego defense mechanism such as sublimation of receiving 2 a target replacement means when experiencing a boost, its distribution in the other direction, the projection is blaming others about distress or desire that is not good, repression is preventing painful thoughts or endanger entry to consciousness, reaction formation which prevents harmful desires when expressed by exaggerating the opposite attitude and behavior used as an obstacle, and diplacement is releasing feeling depressed, venting on the objects that are not so harmful that evokes emotion. Objective: To know the proper coping mechanisms to control violent behavior. Methods: The author uses descriptive method with case studies for 3x24 hours in RSJD. Result: The client is able to control violent behavior in accordance with the Implementation Strategy (SP) violent behavior. Conclusions: Implementation Strategies to control violent behavior can be performed well and coping mechanisms can be achieved with the implementation of the strategy that has been done. Keywords: Mental disorders, Violent behavior, Coping mechanisms.